Utilising biological geotextiles: Introduction to the BORASSUS project and global perspectives - Fullen M. (2017)
Field and laboratory studies indicate that utilisation of biological geotextiles constructed from palm-leaves and other selected organic materials are an effective, sustainable and economically viable soil conservation technique. The three-year plus (1 July 2005-28 February 2009) EU-funded BORASSUS Project (contract no. INCO-CT-2005-510745) evaluated the long-term effectiveness of biological geotextiles in controlling soil erosion and assessing their sustainability and economic viability. These studies progressed in ten countries, both in the 'industrial north' (in Europe) and in the 'developing south' (Africa, South America and South East Asia). The studied countries in the 'developing south' included Brazil, China, The Gambia, South Africa, Thailand and Vietnam. The 'industrial north' countries included Belgium, Hungary, Lithuania and the UK. The main findings of these studies are summarised in this paper and thematic information is presented in the other four papers in this Special Issue. Biological geotextiles offer potentially novel bioengineering solutions to environmental problems, including technologies for soil conservation, sustainable plant production and use of indigenous plants, improved ecosystem management by decreasing deforestation, improving agroforestry and cost-effective biogeotextile applications in diverse environments. Biogeotextiles may provide socio-economic platforms for sustainable development and the benefits for developing countries may include poverty alleviation, engagement of local people as stakeholders, employment for disadvantaged groups, small and medium enterprise (SME) development, earning hard currency, environmental education and local community involvement in land reclamation and environmental education programmes. These benefits are achieved through: (i) promotion of sustainable and environmentally friendly palm-agriculture to discourage deforestation, promoting both reforestation and agroforestry; (ii) construction of biogeotextiles enabling development of a rural labour-intensive industry, particularly encouraging employment of socially disadvantaged groups and (iii) export of biogeotextiles to industrialised countries could earn hard currency for developing economies, based on the principles of fair trade. Research and development activities of the BORASSUS Project have improved our knowledge on the effect of biogeotextile mats on the micro- and macro-soil environments and at larger scales through controlled laboratory and field experiments in diverse environments. © 2011 John Wiley & Sons, Ltd.